Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1097/01.inf.0000130074.56368.4b
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Pneumonitis Caused by Mycoplasma pneumoniae in Pediatric Patients

Abstract: Mycoplasma pneumoniae infection is usually self-limited without severe sequelae. We report 5 pediatric patients with necrotizing pneumonitis caused by Mycoplasma pneumoniae and reviewed the reported cases in the English language. Protracted course of fever and respiratory distress were noted in all 5 patients. Macrolides and adequate chest tube drainage for pleural effusion were the mainstay of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 8 publications
0
44
0
3
Order By: Relevance
“…Although M. pneumoniae infection was traditionally thought to be a self-limited process, more and more severe cases even fatal cases of M. pneumoniae infections were reported in recent years (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although M. pneumoniae infection was traditionally thought to be a self-limited process, more and more severe cases even fatal cases of M. pneumoniae infections were reported in recent years (3)(4)(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…M. pneumoniae pneumonia (MPP) is usually a benign self-limited disease. However, sometimes it may cause various extrapulmonary complications and progress to a severe life-threatening pneumonia (3)(4)(5)(6)(7)(8). These cases might show clinical and radiological deterioration despite of macrolide antibiotic therapy for 7 days or longer (9).…”
mentioning
confidence: 99%
“…It is characterised by necrosis and liquefaction of lung parenchyma, which is thought to be secondary to ischaemia caused by thrombosis of intrapulmonary vessels and can culminate in pulmonary gangrene [89] of single or multiple lobes [74,90]. Historically, the primary causative pathogen was thought to be S. aureus [91] but S. pneumoniae, particularly serotypes 1, 3 9V and 14 [88,89], is now the predominant cause, although M. pneumoniae [92], methicillin-resistant S. aureus and PVL strains of S. aureus [93] have also been implicated. Diagnosis is usually made on CT, as plain chest radiographs will not accurately demonstrate the typical disruption of normal parenchymal architecture where multiple airor fluid-filled cavities replace the normal lung tissue [90].…”
Section: Necrotising Pneumoniamentioning
confidence: 99%
“…Authors concluded that M. pneumoniae related PPE was milder than that was caused by other organisms, but its course was longer 26 . Massive pleural effusion and empyema secondary to M. pneumoniae infection has been reported as case series or single case reports 5,[27][28][29][30][31][32] . In our study, M. pneumoniae related empyema and PPE were required chest tube drainage and tube thoracostomy with intrapleural fibrinolysis that M. pneumoniae related empyema and PPE might be massive.…”
Section: Discussionmentioning
confidence: 99%